O regime jurídico dos contratos das empresas estatais prestadoras de serviços públicos na Lei de Responsabilidade das Estatais – Lei Nº 13.303/2016 - Stroppa, Christianne de Carvalho (2020)
After 18 (eighteen) years of waiting, the Federal Law No. 13,303 of June 30, 2016, was promulgated on the terms of paragraph 1, artigo 173, of the Federal Constitution of 1988. Divided into two major themes - governance rules and corporate regime, on the one hand, and bidding and contract rules, on the other. Called the State-Owned Companies Responsibility Law - LRE, its merit was to solve the problem related to the normative set to be observed by said companies, when performing their contracting. Inspired by the Law of Auction (Federal Law No. 10.520/2002) and the Differential Regime of Public Contracting - RDC (Federal Law No. 12.12.462/2011), when it comes to the bidding process, its main novelty is the subject of contracts, specialy considering the subject of the Federal Law No. 8.666/1993, since it is based on consensuality and not on the presence of exorbitant clauses. Analyzing the rules contained, in particular, in artigos 68 to 84 of the Federal Law No. 13.303/2016, it appears that, apart from the introduction of a new contractual model (TYPICAL CONTRACTS OF STATE-OWNED COMPANIES), it is possible to saystate-owned companies which render public services in non-competitive system may formalize (ATYPICAL) ADMINISTRATIVE CONTRACTS OF STAT-OWNED COMPANIES, with immediate foundation in the Federal Constitution